Matharpacady-22.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Lion’s Den is the home of the Leao family. Built-in 1892, the yellow-painted, two-storied house is located at 85 R Naik Road. It has a sprawling open balcony running along the perimeter of the first floor, with decorative metal grille balusters. The staircase to the first floor is located from the outside (to the left). It is one of the best-preserved houses typical of Indo-Portuguese architecture and has changed little in over 130 years of existence.